Confinement–Unconfinement Transformation of ILs in IL@MOF Composite with Multiple Adsorption Sites for Efficient Water Capture and Release. Issue 13 (17th March 2022) - Gu, Xingping; Han, Guopeng; Yang, Qingyuan; Liu, Dahuan
Abstract: Water adsorption based on porous materials is of fundamental importance in atmospheric water harvesting and dehumidification. Herein, a [BOHmim][Zn2 Cl5 ]@MIL‐101(Cr) composite with multiple adsorption sites is designed to enhance the water adsorption capacity. It is interesting to observe that there is a water‐responsive confinement–unconfinement transformation of ionic liquids (ILs) during the water adsorption and release process. Thus, it can simultaneously overcome the limitation of pore volume in traditional porous materials, and the problem of mass transfer in pure ILs. As a result, the obtained IL@MOF composite achieves a high water adsorption capacity (477 wt%) at 298 K and RH =  95%, which can be released under relatively mild operating conditions (313 K, RH =  40%). This work provides a general way to develop adsorbents for the capture of molecules with high polarity and low dew‐point in combination with the advantages of ILs and metal–organic frameworks (MOFs). Abstract : An IL@MOF composite with multiple adsorption sites is designed and synthesized using [BOHmim][Zn2 Cl5 ] and MIL‐101(Cr) to capture and release water. The composite exhibits a high water adsorption capacity (477 wt%). It can be released at a relatively mild condition, and a water‐responsive confinement–unconfinement transformation of ionic liquids (ILs) occurs during the capture and release process of water.